Analysis Of Cultural Acculturation of Suran Wayang Kulit Among The Samin Community in Blora Regency - Tulas’un, Lakna; Sutinnarto, Sutinnarto; Winarni, Isti (Jurnal Ilmu Komunikasi, 2025)
This study demonstrates how the Suran Shadow Puppet performance serves as a vital instrument for cultural integration within the Samin community in Blora. The performance bridges local wisdom and Samin philosophy with modernization, illustrating how traditional art functions as a mediator of social change while simultaneously preserving cultural identity. By analyzing the role of the Suran Shadow Puppet show, this research broadens academic understanding, provides theoretical insights, and supports cultural preservation in line with the principles of Sustainable Development. The study employs qualitative methods, including literature review, in-depth interviews, and participatory observation of Suran Shadow Puppet performances. The findings reveal that acculturation is manifested through religious, socio-cultural, and communicative dimensions, positioning the Suran Shadow Puppet show not only as entertainment but also as a medium for transmitting the core values of the Samin community. These values emphasize honesty, simplicity, commitment, and solidarity. The study affirms that such performances facilitate adaptation to change without compromising cultural identity, while functioning as an effective means of cultural preservation in the digital era.